(untitled) (Zaporizhzhia Historical Review, 2021)
The country and diasporas researchersí studios which deal with the problem of the Ukrainian lands unity are analysed. In this article the author emphasizes the stages of the Ukrainian people struggle for the uniting of the Ukrainian regions into the single whole state and characterizes the historical work concerning each period. Summarizing above mentioned facts, the author makes the conclusion, that contemporary scientific researches try to give up the essence and the Soviet stereotypes and this fact allows to review the content of the struggle for the unity.